Web-Based Self-Compassion Training to Improve the Well-Being of Youth With Chronic Medical Conditions: Randomized Controlled Trial - Amy Louise Finlay-Jones; Asha Parkinson; Fuschia Sirois; Yael Perry; Mark Boyes; Clare S Rees (JMIR Publications, 2023)
BackgroundUp to one-third of young people live with chronic physical conditions (eg, diabetes, asthma, and autoimmune disease) that frequently involve recurrent pain, fatigue, activity limitations, stigma, and isolation. These issues may be exacerbated as young people transition through adolescence. Accordingly, young people with chronic illness are at a high risk of psychological distress. Accessible, evidence-based interventions for young people with chronic illnesses are urgently needed to improve well-being, support adaptation, and enhance daily functioning. Self-compassion, which is an adaptive means of relating to oneself during times of difficulty, is a promising intervention target for this population. ObjectiveThis study aims to test the efficacy of a 4-week, self-guided, web-based self-compassion training program for improving well-being among young Australians (aged 16-25 years) living with a chronic medical condition. The primary outcomes were self-compassion, emotion regulation difficulties, and coping; the secondary outcomes were well-being, distress, and quality of life. We also sought to test whether changes in primary outcomes mediated changes in secondary outcomes and gather feedback about the strengths and limitations of the program. MethodsWe conducted a single-blind, parallel-group, randomized controlled trial comparing a 4-week, fully automated, web-based self-compassion training program with a waitlist control. Participants were recruited via the internet, and outcomes were self-assessed at 4 (T1) and 12 weeks (T2) after the baseline time point via a web-based survey. A mixed methods approach was used to evaluate the program feedback. ResultsOverall, 151 patients (age: mean 21.15, SD 2.77 years; female patients: n=132, 87.4%) were randomized to the intervention (n=76, 50.3%) and control (n=75, 49.7%) groups. The loss-to-follow-up rate was 47.4%, and program use statistics indicated that only 29% (22/76) of young people in the experimental group completed 100% of the program. The main reported barrier to completion was a lack of time. As anticipated, treatment effects were observed for self-compassion (P=.01; partial η2=0.05; small effect); well-being (P≤.001; partial η2=0.07; medium effect); and distress (P=.003; partial η2=0.054; small-medium effect) at the posttest time point and maintained at follow-up. Contrary to our hypotheses, no intervention effects were observed for emotion regulation difficulties or maladaptive coping strategies. Improvements in adaptive coping were observed at the posttest time point but were not maintained at follow-up. Self-compassion, but not emotion regulation difficulties or coping, mediated the improvements in well-being. ConclusionsMinimal-contact, web-based self-compassion training can confer mental health benefits on young people with chronic conditions. This group experiences substantial challenges to participation in mental health supports, and program engagement and retention in this trial were suboptimal. Future work should focus on refining the program content, engagement, and delivery to optimize engagement and treatment outcomes for the target group. Trial RegistrationAustralian New Zealand Clinical Trials Registry 12619000572167; https://tinyurl.com/5n6hevt International Registered Report Identifier (IRRID)RR2-10.1186/s12889-020-8226-7